Pengaruh Beban Kerja dan Kompensasi Terhadap Turnover Intention Karyawan PT Mukti Indo Utama : The Effect of Workload and Compensation on Employee Turnover Intention at PT Mukti Indo Utama - Sri Lestari; Tri Lestari (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This research was conducted at PT Mukti Indo Utama with the aim of analyzing the influence of workload (X1) and compensation (X2) on employee turnover intention (Y) at PT Mukti Indo Utama. Data was collected through a survey of 40 employees using a questionnaire. This sampling technique uses non-probability sampling using saturated sampling. The sample in this research was 40 employees of PT Mukti Indo Utama. The data analysis method used was the multiple linear regression method using IBM SPSS Statistics V.29 software. This research concludes that: 1) Workload (X1) has no partial effect on turnover intention (Y). 2) Compensation (X2) partially influences turnover intention (Y). 3) Workload (X1) and compensation (X2) simultaneously influence turnover intention (Y) of PT Mukti Indo Utama employees